IMPACTS OF TYPHOON NONA IN THE COASTAL AREAS OF BIRI-LAROSA - Yruma, Elbert; Ogoc, Myrna Nicol (International Journal of Research -GRANTHAALAYAH, 2020)
A descriptive type of study on the impacts of typhoon Nona was conducted from August 2016 to January 2017 in the selected coastal barangays of Biri, Lavezares, Rosario, and San Jose, (Biri-LaRoSa) which form part of the Biri-LaRoSa seascape and landscape of the province of Northern Samar. It focused on the impacts of the typhoon to the coastal environment and its socio-economic effect. Actual field sampling was done for the quantitative assessment of the coastal ecosystems. Participatory Resource Appraisal (PRA) tools were used for the qualitative assessment. Biri area has a total of 23.5% partially damaged trees and 9.4% totally damaged trees in the mangrove ecosystem; 51.7% damage to the seagrass beds; and 79.1% damage to the corals. Lavezares area has a total of 32.5% partially damaged trees and 9.5% totally damaged trees in the mangrove ecosystem; 47.9% damage to the seagrass beds; and 76.5% damage to the corals. Rosario area has a total of 33% partially damaged trees and 5.8% totally damaged trees in the mangrove ecosystem; 47.6% damage to the seagrass beds; and 36.1% damage to the corals. San Jose area has a total of 39.6% partially damaged trees and 7.6% totally damaged trees in the mangrove ecosystem; 48% damage to the seagrass beds; and 56.8% damage to the corals. Typhoon Nona greatly affected the ecosystems in the sampling sites and in turn affected the socio-economic conditions of ‘the locals, especially those who are dependent on the coastal resources both for food and income. Both results of the PRA and actual field assessment support this claim.